2019
DOI: 10.1016/j.dadm.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 lowers age at onset in patients with frontotemporal dementia and tauopathy independent of amyloid‐β copathology

Abstract: Introduction Apolipoprotein E (ApoE) is the most important genetic risk factor for Alzheimer's disease (AD), with ApoE4 thought to enhance and accelerate amyloid‐β (Aβ) pathology. ApoE4 has recently been described to increase neurodegeneration in a mouse model of frontotemporal dementia (FTD), in vitro, and in patients, demonstrating that ApoE4 modifies tauopathy independently of Aβ. This raises the question whether ApoE genotype also modifies the clinical phenotype in patients with FTD with tau pathology. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Other genetic or environmental factors affecting age at symptom onset and at death in individuals with MAPT mutations have not yet been well studied. 24 Despite being statistically significant, correlation coefficients were low in the GRN group for the com parisons between individual age at symptom onset and parental and mean family age at symptom onset. The variability in age at symptom onset and age at death for individuals with GRN mutations was not accounted for particularly by either the individual mutation or family membership.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Other genetic or environmental factors affecting age at symptom onset and at death in individuals with MAPT mutations have not yet been well studied. 24 Despite being statistically significant, correlation coefficients were low in the GRN group for the com parisons between individual age at symptom onset and parental and mean family age at symptom onset. The variability in age at symptom onset and age at death for individuals with GRN mutations was not accounted for particularly by either the individual mutation or family membership.…”
Section: Discussionmentioning
confidence: 85%
“…Significant differences were also found between the three genetic groups in the variability of interfamily and intrafamily age at death (both p<0•0001; appendix p 49). Family membership explained 74% (95% CI 65-82) of this variability in individuals with MAPT mutations, but only 20% (12-30) in those with GRN mutations and 19% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) in those with C9orf72 expansions. We also found a significant difference between the GRN and MAPT groups in the betweenmutation variability in age at death (p<0•0001): in the GRN group, only 9% (95% CI 3-21) of the variability was explained by the specific mutation, whereas in the MAPT group, 61% (47-73) of the variability was explained by the specific mutation.…”
Section: Resultsmentioning
confidence: 99%
“…In AD, APOEε4 only associates with tau pathology in the presence of amyloid pathology [86]. However, in frontotemporal dementia with MAPT mutations that lead to familial tauopathy, APOEε4 lowers the age of onset independent of amyloid plaques [168]. In contrast, another study found that APOEε2 was associated with increased tau pathology burden in PSP [327].…”
Section: Bidirectional Effects Of Tau Pathology and Microglial Neuroimentioning
confidence: 99%
“…For Aβ x-40 ELISA, HJ2 (anti-Aβ [35][36][37][38][39][40] ) was used as a capture antibody and for Aβ x-42 ELISA, HJ7.4 (anti-Aβ [37][38][39][40][41][42] ) was used as a capture antibody. HJ5.1-biotin (anti-Aβ [13][14][15][16][17][18] ) [33,34] was used as the detecting antibody for both Aβ ELISAs.…”
Section: Sandwich Elisamentioning
confidence: 99%
“…Emerging data indicate that APOE not only affects AD risk, but also severity of pathology in dementia with Lewy bodies and neurodegeneration in tauopathies [11][12][13][14]. In particular, microglia-derived apoE appears to regulate the inflammatory response [11,[15][16][17], suggesting that the cellular source of apoE in both the brain and periphery has distinct functions in different diseases.…”
Section: Introductionmentioning
confidence: 99%